Analisis Pola Pengembangan Paragraf dan Penggunaan Deiksis dalam Artikel Opini di Harian Umum Kompas - Eka Purnama Sari (Diskursus: Jurnal Pendidikan Bahasa Indonesia, 2021)
The objective of the Research is to describe the development pattern of the paragraph and deixis used in opinion articles in the Kompas daily newspaper. The method used in this study is qualitative descriptive, that of solving problems by collecting, analyzing, and interpreting data. The sources of data in this study are words, sentences, and paragraphs. Conclusions derived from the analysis of the development pattern of paragraph and the use of deixis in the opinion articles in Kompas daily newspaper, found that deixis of space is the most widely used in opinion opinion articles and special-generational development patterns as opening and generalized development patterns used more frequently in opinion articles. This is seen from as many as 25 opinion articles use space deixis, and 20 opinion articles use specialized, generalized, generalized development patterns as the corresponding development pattern to its opening and closing. Key words: paragraph development pattern, deixis, opinion article